Influence of buccal mucosa width/height ratio, emergence profile and buccal bone width on peri-implant tissues: a prospective one-year study - Yiman Tang; Juan Wang; Lixin Qiu; Huajie Yu (BMC Oral Health, 2025)
Abstract Background The stability of soft and hard tissues surrounding the implant is not only a matter of aesthetics, but also affects the long-term stability of the implant. The present study was to explore the influence of buccal mucosa width/height (W/H) ratio, emergence profile and buccal bone width on peri-implant soft and hard tissue changes in the posterior region. Methods Fifty-eight posterior implant restoration cases were recruited in this study. Evaluations were performed at the time of restoration placement (T0), and 1 year later (T1). Buccal mucosa width (BMW), buccal bone width (BBW), implant buccal inclination angle, and emergence angle were evaluated. The variables that may affect buccal mucosa recession (MR) as well as vertical bone loss (VBL) were analyzed. Results The BMW at baseline was 2.93 ± 1.01 mm. The BBW at baseline was 1.50 ± 0.82 mm. The buccal mucosa W/H ratio at 1 year (1.23 ± 0.38) was significantly lower than that at baseline (1.42 ± 0.45). Buccal MR was − 0.22 ± 0.47 mm while VBL was 0.81 ± 0.80 mm. The correlation between MR and initial BMW (r=-0.381), initial W/H ratio (r=-0.422), BBW (r=-0.290) was statistically significant. The correlation between VBL and initial BMW (r=-0.421), initial W/H ratio (r=-0.305), implant buccal inclination angle (r = 0.507), BBW (r=-0.556) was statistically significant. Conclusions Within the scope of this study, implant sites in the posterior region presenting a thin BMW, a thin BBW, and a small W/H ratio are more prone to exhibit buccal mucosa recession and vertical bone loss.